Ethnobotanical Review of Selected Medicinal Plants in Guam for the Treatment of Urinary Tract Ailments and Their Pharmacological Properties - Sahena Ferdosh (MDPI AG, 2023)
The Chamorro healers of Guam have more than a thousand years of history of using herbs and medicinal plants for the treatment of common ailments. The objective of this study is to review the bioactive compounds and pharmacological properties of medicinal plants which are used for urinary tract health by local healers. Literature searches were performed using Google Scholar, ScienceDirect, PubMed, and SpringerLink, by using several keywords, including "medicinal plants in Guam", "traditional uses", "bioactive compounds", "pharmacological properties", and "urinary tract infections". This review highlights the traditional uses, bioactive compounds, and pharmacological properties of five medicinal plant species, namely Euphorbia hirta, Phyllanthus amarus, Premna serratifolia, Psidium guajava, and Urena lobata. Phenolics, alkaloids, terpenoids, essential oils, and polypeptides are the leading secondary metabolites reported in different plant extracts, which have been found to have significant antimicrobial, antioxidant, anti-inflammatory, antidiabetic, and anticancer properties. The therapeutic claims made about medicinal plants in Guam are well supported by the literature, having similar applications and pharmacological properties in other regions of the world. These medicinal plants have a lot of unexplored potential that might be utilized to develop more potent drugs for the treatment of infectious diseases, as well as food and herbal supplements.